Modified TiO2 Photocatalyst for CO2 Photocatalytic Reduction: An overview - Hamidah, Abdullah; Khan, Maksudur R.; Huei, Ruey Ong; Zahira, Yaakob (Elsevier, 2017)
The photocatalytic pathway to reduce carbon dioxide (CO2) to fuel, an artificial photosynthesis process, is a futuristic and ultimate way to combat the energy crisis and CO2 emission issues. The most widely used catalyst for photocatalytic reactions is titanium dioxide (TiO2) due to its availability, chemical stability, low cost and resistant to corrosion. Although TiO2 photocatalyst suffers due to its wide band gap (only can be activated under ultraviolet light irradiation) and high electron-hole recombination rate, it remained as a precursor for the development of visible light responsive materials for CO2 reduction through different modifications, such as doping of metal, nonmetal, semiconductors etc. There is a significant improvement in CO2 conversion using the visible light responsive TiO2 based catalysts. The product distribution due to the photocatalytic reduction of CO2 highly depends on the band gap and band edges of the catalyst. The understanding in the mechanistic pathway of CO2 reduction is very important to design the catalyst for the production of desired product. This present paper provides an overview of research and development of TiO2 based photo-catalysts for CO2 reduction and focuses on the improvement of the photocatalyst based on the band gap engineering, charge transfer and CO2 adsorption. Moreover, the challenges and future prospect in the developing modified TiO2 for photocatalytic reduction of CO2 has also been discussed.